Leveraging AI To Enhance Green Marketing Strategies - Agustiawan Djoko Baruno; Meithiana Indrasari (Penerbit Jurnal Indonesia, 2025)
Abstract: The increasing focus on sustainability and environmental conservation has reshaped the marketing landscape, prompting businesses to adopt green marketing strategies. Simultaneously, advancements in Artificial Intelligence (AI) have transformed traditional marketing approaches, offering data-driven insights and innovative tools. This study explores the integration of AI technologies into green marketing to enhance its effectiveness and sustainability impact. It examines how AI-powered tools, such as predictive analytics, machine learning, and automation, can optimize green marketing strategies by enabling precise targeting, real-time campaign adjustments, and sustainability performance measurements. Through an analysis of existing literature, case studies, and real-world applications, this research highlights AI's potential to improve consumer engagement, build trust in eco-friendly brands, and overcome implementation challenges in diverse markets. The findings provide actionable insights for businesses, policymakers, and marketers, emphasizing the role of AI in advancing green marketing initiatives globally. This study bridges the gap between AI innovation and sustainable marketing, offering a comprehensive framework for leveraging technology to achieve environmental and business goals.